Vigabatrin Intractable Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The relationship between vigabatrin dosage and plasma concentrations, platelet GABA-transaminase inhibition and seizure reduction in 16 children with refractory epilepsy was studied at the University of Cantabria, Santander, Spain.